Credit Rationing and Private Transfers: Evidence from Survey Data - Cox, Donald; Japelli, Tullio (The Review of Economics and Statistics, 1990)
This paper investigates the connection between credit rationing and private intergenerational transfers. The research is motivated by the idea that private transfers may be a source of funds for consumers who have difficulty borrowing from financial intermediaries. This idea has important implications for consumer behavior, and economists have begun to think about it, but they have given it little empirical attention. Using the 1983 Survey of Consumer Finances, we find that private transfers do tend to be targeted toward consumers who face credit rationing. But we also find that a substantial fraction of U.S. consumers are liquidity-constrained even if one allows for the possibility of private transfers.